Human CD8(+)CD28(−) T suppressor cells expanded by common gamma chain (γc) cytokines retain steady allospecific suppressive capacity in vivo - Liu, Guihuan (BMC Immunol, 2020)
BACKGROUND: CD8(+)CD28(−) T suppressor (Ts) cells play critical role in transplant tolerance. Our previous study has generated CD8(+)CD28(−) Ts cells in vitro which exert robust allospecific suppressive capacity in vitro. RESULTS: CD8(+)CD28(−) Ts cells were expanded by stimulating human CD8(+) T cells with allogeneic antigen presenting cells in the presence of the common gamma chain cytokines IL-2, IL-7 and IL-15 in vitro, and were further verified in vitro through day 7 to 11 for their persistency of the allospecific suppressive capacity. When CD8(+)CD28(−) Ts cells were adoptively transferred into NOG mice, their capacity to inhibit CD4(+) T cell proliferation in allospecific manner remained potent on 11 days after their injection. The mechanisms for expansion of CD8(+)CD28(−) Ts cells by the common gamma chain cytokines were investigated. These included promoting CD8(+)CD28(−) T cells proliferation, converting CD8(+)CD28(+) T cells to CD8(+)CD28(−) T cells and decreasing CD8(+)CD28(−) T cell death. Furthermore, the expanded CD8(+)CD28(−) Ts cells showed upregulation of the co-inhibitory molecule Tim-3 and down-regulation of the cytotoxic molecule granzyme B. CONCLUSIONS: In summary, these results demonstrated that the in vitro-expanded human CD8(+)CD28(−) T cells retained potent allospecific suppressive capacity in vivo and depicted multiple mechanisms for the expansion of Ts cells, which might promote further bench to clinic research.